INCIDENCE OF ESOPHAGEAL CANCER AMONG MEN AND WOMEN IN THE REPUBLIC OF KARAKALPAKISTAN - Islambek A. Kudiyarov; Nafisa R. Mirvalieva; Abror Sh. Shomurodov (Central Asian Journal of Medicine, 2024)
The article is based on a study of the prevalence of esophageal cancer in the Republic of Karakalpakstan. During the study, the dynamics of the incidence of esophageal cancer among men and women in the Karakalpakstan Republic and regions was compared. During the study period (2011-2021), 1672 patients with newly diagnosed RP were registered in the Republic of Karakalpakstan. Of these, 38.6% - in men and 61.4% in women, women had one and a half times more cases than men. But in the last 5 years (2017-2021) in the male and female population of the Republic of Karakalpakstan, intensive indicators in the incidence of esophageal cancer have decreased compared to the previous years.